Whether joint leisure time physical activity and dietary quality alleviates metabolic syndrome and its components: evidence from the National Health and Nutrition Examination Survey (2007–2018) - Jingyi Xie; Bin Wang (PLoS ONE, 2025)
Objectives The incidence of metabolic syndrome (MetS) is increasing, which is one of the major threats to human health. Whether joint leisure time physical activity (LTPA) and dietary quality (DQ) can reduce the risk of developing MetS and its components is worth exploring. Therefore, this study aimed to investigate the individual and combined effects of LTPA and DQ on MetS and its components. Methods Data were extracted from the National Health and Nutrition Examination Survey from 2007 to 2018. LTPA was classified as inactive, insufficiently active (IA), weekend warrior (WW), and regular active (RA); DQ was categorized as high dietary quality (HDQ) and low dietary quality (LDQ). Afterwards, population characteristics of MetS were analyzed. Then, univariate and multivariate logistic regression were used to analyze individual and combined effects of LTPA and DQ on MetS and its components. Subgroup analysis and restricted cubic spline (RCS) were used to examine the robustness and non-linearity. Results This study included 31,482 adults aged 20 or older. Results showed that RA, HDQ and RA&HDQ were significantly negatively correlated with MetS and its components. IA&HDQ was significantly and negatively correlated with MetS, waist circumference and high-density lipoprotein cholesterol. WW&HDQ was not significantly associated with MetS, but was significantly negatively linked to fasting glucose and blood pressure. No significant interaction effect was observed in subgroup analysis. RCS analysis revealed a significant non-linear negative correlation between LTPA and MetS. Conclusions This research indicates that RA and HDQ alone or in combination are associated with a lower risk of developing MetS and its components and could serve as effective preventive and therapeutic strategies against MetS and its associated risk factors. The decline in MetS risk become even more significant after exercise for 500 min/week. Similar trends are observed among fasting glucose, blood pressure, and triglyceride levels.